An investigation of the salary received during COVID- 19 by low-paid employees working in private schools in Nepal - Singh, Daman Bahadur (Journal of Development Review, 2023)
Covid-19, which started in Uhan in China at the end of 2019, spread all over the world at the beginning of 2020. Which Nepal could not remain untouched. In March 2020, the government began to lock down on the spread of corona in Nepal. In addition to teachers, various staff is also employed in each private school. Among the employees, low-salary paid employees like drivers/attendants, Peon, Aaya, swipers, and Security Guard. These types of employees were found to be providing various services on the school premises even during the non-operation of the school during the lockdown period. To examine the salary of low-paid employees of a private school in Kathmandu Valley (Kathmandu, Lalitpur, and Bhaktapur districts) before and during the COVID-19 period. Examine the significant difference between the mean salary received before the pandemic and during the pandemic period are the two main objectives of this research. The population during this research was private schools running in Kathmandu valley including Kathmandu, Lalitpur, and Bhaktapur districts. Altogether there were 1500 private schools in Kathmandu valley. Out of them, five secondary schools from each district were purposively selected for the research. In this research quantitative research design was adopted. In the sampling design, the nonprobability sampling technique (purposive technique) was applied to select the required number of schools from each district. The selected school’s low-salary paid school staff like a security guard, Driver and conductor, Aaya, peon, and swiper were categorized, and from each category, 15 respondents were selected as a sampling unit from each selected district. The total number of respondents was 60. After analyzing the data before the pandemic, the salary of a security guard, Driver/conductor, peon/Aaya, and sweeper were 20333.33, 9466.66, and 7933.34, and during the pandemic were 5333. 33, 5533. 334033. 33, 3500,.respectively. Variations of salary provided to them by different schools were very high. There is a significant difference in the mean salary received by different low-salary paid staff before and during the pandemic period.